Exploring the Impact of Immersive Projection Art on Visitor Behavior and Engagement - Zhao, Li; Qi, Jianming; Wang, Jian (Journal of Social Science and Humanities, 2025)
This study examines the impact of immersive projection art on visitors’ emotional, cognitive, and behavioral engagement, using case studies of the China Grand Canal Museum, teamLab Planets in Japan, and ARTE MUSEUM in South Korea. The results indicate that historical and cultural venues enhance cognitive comprehension, art exhibitions emphasize emotional and behavioral interactions, and nature-themed experiences evoke deeper resonance through multisensory stimulation. Immersive projection fosters emotional immersion and cognitive absorption, enhances the depth of interaction, and stimulates exploratory behavior. This study provides valuable insights for future venue designs in terms of technology integration, multisensory engagement, and content innovation, contributing to the creation of more engaging and educational immersive experiences.